Accreditation Readiness and Institutional Quality: An Assessment of Stakeholder Experiences - Mary Rose F. Montano; Ronald A. Gonzales; Simplicio P. Alba; Richie V. Mendoza; Anna Rhea C. Opeña; Armando A. Salenga Jr.; Francis Eduard T. Malitig (Research Synergy Foundation, 2026)
Accreditation is a vital mechanism for ensuring quality assurance, institutional credibility, and continuous improvement in higher education. This study examined accreditation readiness, stakeholder satisfaction, and perceived challenges at a Philippine higher education institution following the accreditation visit by the City College of Calamba (CCC) during the second semester of Academic Year 2024–2025. Using a convergent parallel mixed-methods design, quantitative data were collected from 525 administrators, faculty members, non-teaching personnel, and students, complemented by qualitative thematic analysis of open-ended responses. Results indicated a high level of accreditation readiness (M = 4.23, Excellent) and stakeholder satisfaction (M = 4.30, Very Satisfied), with administrators reporting the most favorable perceptions. Challenges were rated as considerable (M = 3.64), primarily related to administrative support, time constraints, and resource limitations. No significant differences were found across stakeholder groups, suggesting a shared institutional experience. A strong positive relationship was found between accreditation readiness and stakeholder satisfaction (r = .894, p < .001), while the relationship between readiness and perceived challenges was negligible (r = .133, p < .001). Thematic analysis yielded four major themes: institutional proactivity, operational barriers, integrated support systems, and empowered teamwork, which reinforced the quantitative findings. The results highlight that preparedness enhances stakeholder satisfaction but does not fully mitigate operational challenges. The study contributes a stakeholder-centered perspective to Philippine accreditation literature and proposes an action plan to strengthen accreditation readiness through inclusive, coordinated, and sustainable quality assurance practices.